Design of Power Transformer with Frequency 1 Khz - Franko, Marek; Kucera, Roman; Biel, Zdeno; Holcek, Roman; Frivaldsky, Michal (Communications - Scientific Letters of the University of Zilina, 2023)
This paper deals with the noise level of power transformers operating at a middle frequency from 800 Hz to 2000 Hz. The factors that influence the noise produced by power transformers are size, design and operating conditions. The research shows that the noise level of power transformers can vary widely depending on these factors. The paper discusses an overview of different types of power transformers core and their impact on the transformer's noise performance. This paper describes the design of a middle-frequency power transformer, its material composition and the design of the magnetic circuit and windings, operating in the frequency range 800 to 2000 Hz, with a capacity of 200 kVA, air-cooled, to be fed from a suitable frequency converter, characterized by reduced noise. The proposed solution allows implementation of galvanically isolated DC-DC converters for auxiliary traction drives and other DC-DC converters.
Keywords: power transformer; transformer-based noise; soft magnetic materials nanocrystalline materials